Short Communication: Age and growth of elongated mudskipper, Pseudapocryptes elongatus (Cuvier, 1816) from Sundarbans, India - GOPALAN MAHADEVAN; PALANIVEL BHARATHIRAJAN; VELAYUTHAM RAVI; MOJTABA POULADI; MARYAM MIRZAEI VAND KHANGHAH (Society for Indonesian Biodiversity, 2019)
Mahadevan G, Bharathirajan P, Ravi V, Pouladi M, Mirzaei Vand Khanghah M. 2019. Short Communication: Age and growth of elongated mudskipper, Pseudapocryptes elongatus (Cuvier, 1816) from Sundarbans, India. Biodiversitas 20: 85-90. The estimation of age and mathematical expression of fish growth is complex and debated subject in fishery sciences. Growth parameters of elongated mudskipper, Pseudapocryptes elongatus were estimated based on the length frequency data using FiSAT II software (several tools such as Powell-Wetherall method, ELEFAN and von Bertalanffy growth estimates). Samples were collected from Sundarbans mangroves using gill and cast nets and by hand picking. The length-frequency (LFQ) of P.elongatus was recorded from January 2014 to December 2015 and the above tools estimated the growth parameters (L?, K and t0) from the progression of LFQ modes through time. L? and K values of males were 220.50 mm and 1.3 yr-1, respectively and similarly, L? and K values of females were 221.05 mm and 1.21 yr-1, respectively. The t0 values estimated for males and females were-0.1915 years and-0.1661 years, respectively. The estimated growth performance index (?) values for males and females of P. elongatus were 4.394 and 4.503, respectively. The lifespan of both the sexes was found to be 4+ years.